Corporate governance, firm value, institutional, ownership and corporate social responsibility - Mita Nur Octaviani; Ludwina Harahap (LPMP Imperium, 2022)
Research in the area of corporate governance (CG) conducted so far, focusing more on the board of commissioners, board of directors, and audit committee on the achievement of corporate value; institutional ownership mechanisms are still rarely analyzed. Therefore, this study explores more roles of institutional ownership in mitigating manager behavior not to impede the achievement of corporate goals and the creation of corporate value. Other governance mechanisms, namely external governance, can also discipline managers to help achieve the company's goals of improving shareholders' prosperity using corporate CSR proxies. With a sample of 13 companies registered in the mining sector for 5 years, researchers tried to test whether internal and external governance could positively affect the company's value. The results show that internal and external governance positively affect the company's value, except for the influence of the audit committee, which shows its insignificance to the company's value. Moreover, independent commissioners, board of commissioners, institutional ownership, and CSR positively significantly affect the company's value. The result may contribute to the development of corporate governance literature and support to the authority board to strengthen the regulations which is protect the investors, shareholders and also stakeholders elsewhere.